2021
DOI: 10.36778/jesya.v4i1.333
|View full text |Cite
|
Sign up to set email alerts
|

Application of Risk Management to the Level of Financial Efficiency in BPD JAWA TENGAH

Abstract: Efficiency is one measure of bank performance. The efficiency of a bank is influenced by how management manages risk. This study measures the level of efficiency of conventional banking at PT Bank Pembangunan Daerah Jawa Tengah and the effect of financing risk, operational risk, and liquidity risk on the level of efficiency. Efficiency is measured by the Operational Expenditure method from Operating Income. The results of the calculation seen from the Operational Expenditure financial ratio report data from Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, it is necessary to establish a scientific early warning mechanism, and risk measurement provides the basic basis for early warning. The function of asset value evaluation is divided into two types in this system according to the purpose of evaluation, namely, risk of credit value fluctuation type and liquidity risk assessment [11][12].…”
Section: Risk Assessment Management Function 1) Asset Value Risk Assessmentmentioning
confidence: 99%
“…Therefore, it is necessary to establish a scientific early warning mechanism, and risk measurement provides the basic basis for early warning. The function of asset value evaluation is divided into two types in this system according to the purpose of evaluation, namely, risk of credit value fluctuation type and liquidity risk assessment [11][12].…”
Section: Risk Assessment Management Function 1) Asset Value Risk Assessmentmentioning
confidence: 99%
“…The results showed that the companies' positioning in the sample changed. Luthfan et al [ 7 ] noted that efficiency was an indicator of bank performance; a bank's efficiency was affected by how management manages risk. The author measured the impact of financing risk, operational risk, and liquidity risk on the level of efficiency.…”
Section: Introductionmentioning
confidence: 99%